197k views
2 votes
4+3 (x-7) = 9- (x+6)

1 Answer

3 votes

STEP 1 : Equation at the end of step 1

(4 + 3 • (x - 7)) - (3 - x) = 0

STEP 2 : Pulling out like terms 3.1

Pull out like factors : 4x - 20 = 4 • (x - 5) Equation at the end of step 3 : 4 • (x - 5) = 0

STEP 3 : Equations which are never true 4.1

Solve : 4 = 0 This equation has no solution. A a non-zero constant never equals zero. Solving a Single Variable Equation: 4.2

Solve : x-5 = 0

Add 5 to both sides of the equation : x = 5

Answer: x=5

User Rluba
by
5.1k points